Sports law: students’ perception of the relevance of learning legal aspects in sports and recreation amongst sport students in UiTM Negeri Sembilan, Seremban Campus / Mohd Syahril Ibrahim, Nur Haidar Hanafi and Nor Fadzlina Nawi - Ibrahim, Mohd Syahril; Hanafi, Nur Haidar; Nawi, Nor Fadzlina (Universiti Teknologi MARA, Negeri Sembilan, 2016)
Sports constitute an important cultural phenomenon and in modern day sports now have its own complex rules, are highly organized and may involve various areas of law. These laws affecting sports and recreation management include liability for sporting injury and damage, sports and media law, professional athletes’ contract of employment, and the issue of doping involving performance-enhancing drugs. Having said that, in Malaysia, generally, there is still little awareness of how law affects sports and recreation management not only among the public, but also the athletes. The Faculty of Sports Science and Recreation (FSR) of UiTM in acknowledging the importance of these areas of law in sports, designed their programs’ curriculum to include “Legal Aspects in Sports and Recreation” and “Law Relating to Sports and Recreation”, as compulsory subjects for students enrolled in their Diploma in Sport Studies and Degree in Sports Management. This research is conducted to ascertain the students’ perception on the relevance of learning these subjects towards enhancing the knowledge on sports law in their related field of works. The paper presents the findings of the students’ perceptions on the relevance of learning these subjects in their respective programs at the FSR in UiTM, Seremban Campus.